Behind the scenes of hospitality: Crafting memorable experiences as an intern in Hilton Cartagena (2023)
Through this paper I aim at describing my internships at the Front Desk Department of Hilton Cartagena. The Front Desk serves as the central hub where efficiency meets warmth, and seamless operations lay the foundation for unforgettable stays. This internship has provided me with a unique opportunity to delve into the intricacies of front desk management. The purpose of this internship report is to reflect on the invaluable experiences gained, the skills honed, and the lessons learned throughout this ransformative period. As I delve into the following pages, I will share insights into the challenges overcome, the achievements celebrated, and the impact that this internship has had on my personal and professional development. Through this report, I hope to convey the essence of my time at the Front Desk of the HIlton Cartagena and showcase the influence it has had on my understanding of hospitality, customer service, and the art of creating lasting impressions.